Study of Pore Fractal Structure and Combustion Performance on Efficient Compound Coal - Zhang, Xiang-Lin; Yang, Hong-Tao; Liu, Na (Asian Journal of Chemistry, 2013)
This paper is using coal, coal slurry and coal gangue of Huaibei mining area as efficient complex coal blending samples, carrying on the study that the pore fractal structure has effect on supercritical fluidized bed combustion, which shows that the amount of coal gangue has great effect on compound coal quality; fractal dimension of compound coal along with a single coal ratio change presents a monotone change and when the fractal dimension from 2.429 gradually increases to 2.518, the ignition temperature from 586 ºC falls to 457 ºC, easy ignition burning; when the amount of coal gangue of compound coal from 10 % falls to 30 %, the ash melting point rises from 1370 ºC to 1450 ºC, the slag-bonding intensity decreases when they are burning.